Learners’ Level of Difficulty in Using Mother Tongue-Based Instruction on Mathematics and Metrobank-MTAP-DepEd Math Challenge - Mula, Richard S. (Future Science / FSH-PH Publications, 2025)
The main thrust of the study was to determine the learners’ level of difficulty in using Mother Tongue Based Instruction on the Metrobank-MTAP-DepEd Math Challenge to their Mathematics and MTAP performances of 195 Grades 3 learners in public elementary schools of Tubigon East and West Districts, Tubigon, Bohol. This research used quantitative methods through descriptive and corre-lational designs using the survey questionnaire that was used to collect the data from Grade 3 learners in 17 public elementary schools in Tubigon East District and 14 public elementary schools in Tubigon West District. This also included all the primary schools with multigrade classes in the said districts. The study used the Mann Whitney U Test to test the significant difference between the learners’ level of difficulty in using Mother tongue-based instruction on the Metrobank-MTAP-DepEd Math Challenge and the learners’ profile. Results of the investigation unfolded that there is a signifi-cant relationship between the level of difficulty in using Mother tongue-based instruction on the Metrobank-MTAP-DepEd Math Challenge and the learners’ profile with a p-value of .000. The result of the study led to the conclusion that using the mother tongue in teaching Mathematics significantly impacts pupils' performance in the Metrobank-MTAP-DepEd Math Challenge competition, often leading to lower scores; where the competition's questions are pre-sented in English, a language quite different from the student's first language,